2022
DOI: 10.3390/jcm11133653
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Carotid Intima–Media Thickness in Physically Active Young Adults: CHIEF Atherosclerosis Study

Abstract: Background: The relationship of cardiorespiratory fitness (CRF) with subclinical atherosclerosis affected by the body adiposity has been observed in children, whereas this relationship remains unclear in young adults. Methods and Results: A total of 1520 military recruits, aged 18–40 years, were included in Taiwan in 2018–2020. All subjects underwent detailed physical and blood laboratory examinations. CRF was evaluated by time for a 3000 m run, and subclinical atherosclerosis was evaluated by intima–media thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Moreover, most of the increased LV diastolic functions related to exercise training directed from reduced heart rate (Lin, Liu, Tsai, et al, 2022;Lin, Lloyd-Jones, Colangelo, et al, 2022;Lin, Tsai, Chang, et al, 2022;Lin, Tsai, Han, et al, 2022), which revealed an association with significant cIMT in this study, reconfirming the physical effects on both LVM and cIMT.…”
Section: The Ecg and Echocardiographic Markers For Significant Caroti...supporting
confidence: 79%
See 3 more Smart Citations
“…Moreover, most of the increased LV diastolic functions related to exercise training directed from reduced heart rate (Lin, Liu, Tsai, et al, 2022;Lin, Lloyd-Jones, Colangelo, et al, 2022;Lin, Tsai, Chang, et al, 2022;Lin, Tsai, Han, et al, 2022), which revealed an association with significant cIMT in this study, reconfirming the physical effects on both LVM and cIMT.…”
Section: The Ecg and Echocardiographic Markers For Significant Caroti...supporting
confidence: 79%
“…Among patients with hypertension, higher BP level is a crucial shared risk factor and plays a major role in the positive relationship between LVM and cIMT (Meijs et al, 2009). In tactical athletes, such as our military personnel, prior studies have revealed that physical fitness could increase LV muscle hypertrophy and diastolic function (Lin, Liu, Tsai, et al, 2022;Lin, Lloyd-Jones, Colangelo, et al, 2022;Lin, Tsai, Chang, et al, 2022;Lin, Tsai, Han, et al, 2022;Liu et al, 2022). Greater cardiorespiratory fitness TA B L E 2 Echocardiographic findings of participants with ultrasonography for carotid intima-media thickness and muscular strength levels have revealed an inverse association with lower cIMT levels (Lin, Liu, Tsai, et al, 2022;Lin, Lloyd-Jones, Colangelo, et al, 2022;Lin, Tsai, Chang, et al, 2022;Lin, Tsai, Han, et al, 2022).…”
Section: The Ecg and Echocardiographic Markers For Significant Caroti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiorespiratory fitness (CRF) is inversely associated with the risk of metabolic syndrome, diabetes mellitus, cardiovascular diseases (CVD), and mortality in the general population ( Carnethon et al, 2009 ; Mehta et al, 2020 ; Wang et al, 2021 ; Lin et al, 2022 ; Sui et al, 2022 ). Obtaining greater CRF levels for sedentary individuals has been proposed as one of the major preventive measures to reduce the severity and burden of atherosclerosis in developed countries ( Lavie et al, 2019 ; Sanchis-Gomar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%